Studi Kepuasan Pelanggan Terhadap Peraturan Sistem Cara Bayar Parkir E-Money/Tapcash Pada Pelanggan RSUP Dr. Sardjito Yogyakarta - Mahfud Sidiq, Ridho; Budi Retnoningrum, Yuana; Selintia, Sela (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This study aims to examine customer satisfaction with the implementation of an E-Money/Tapcash-based parking payment system at RSUP Dr. Sardjito Yogyakarta. The research adopts a quantitative approach using a simple linear regression method to analyze the relationship between customer satisfaction (variable X) and the digital payment system (variable Y). Data were collected through questionnaires from 100 outpatient respondents. The analysis results indicate that customer satisfaction significantly influences the digital payment system, with an R-square value of 67.3%. This study concludes that customer satisfaction has the potential to enhance the adoption of cashless payment systems (digital payments), despite challenges in technology adoption among users.